Navigating disruptive experiences in combat sports: perspectives of Brazilian, Portuguese, and Spanish masters on emotional control, resilience, and well-being - Santos, Maria Gabriela dos; Santos, Yan Lazáro; Telles, Thabata Castelo Branco; Barreira, Cristiano Roque Antunes (Frontiers in Sports and Active Living, 2025)
No other sport has such a fine line with violence as combat sports, but it is understood that in order to improve the practitioner there are psychological-combative transitions between the phenomena of playing, corporal fighting and brawling. This is not to omit the relevance of this proximity, but to try to understand it. So how can this experiential proximity between sport and violence lead to the development of the practitioner, from the masters’ perspective? This study adopted an empirical-phenomenological approach, in which interviews were conducted through a mode of suspensive listening. Following this, Psychological Reduction and Intentional Crossing were employed to analyze 47 interviews with teachers from all five regions of Brazil, the northern region of Portugal, and the northwestern and central-northern region of Spain. For now, across the three cultures investigated, we have identified and described four Units of Meaning that represent different facets of the manifestations of the phenomenon in question: 1. Combative Intensification; 2. Disruptive Situations; 3. Interventions by the instructor; 4. Changes in the Process. It is concluded that, from the teacher's perspective and through the comparison of three different countries, for the practitioner to develop, the combative situation must be ethically and pedagogically grounded in the necessary intensification that allows the learner to maintain the fighting spirit. However, when the teacher perceives that the student is not self-controlled in the moment, they intervene with the aim of promoting change and supporting the student's development in the practice of combat sports.